2017
DOI: 10.1038/srep42541
|View full text |Cite
|
Sign up to set email alerts
|

Role of endothelial nitric oxide synthase and endothelin-1 polymorphism genes with the pathogenesis of intraventricular hemorrhage in preterm infants

Abstract: In the pathogenesis of neonatal intraventricular hemorrhage (IVH) in preterm infants, an important role is played by changes in venous and arterial cerebral flows. It has been shown that the ability of autoregulation of cerebral flows in response to variations in arterial blood pressure in preterm infants is impaired. This impaired autoregulation causes an increased risk of germinal matrix rupture and IVH occurrence. We examined three polymorphisms of genes, related to regulation of blood flow, for an associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
(46 reference statements)
0
13
0
Order By: Relevance
“…From our previous studies, we were able to highlight the significance of methylenetetrahydrofolate reductase (MTHFR 1298A > C) polymorphism as a possible risk factor for IVH due to increased levels of plasma homocysteine [35]. Similarly, there was approximately a 3.5-fold increased risk of developing IVH in preterm infants with the GT eNOS 894G > T polymorphism of endothelial nitric oxide synthase (eNOS), a gene associated with blood flow [12]. Prasun P et al examined polymorphisms in VEGF and showed a higher prevalence of IVH in infants with GA/AA and AA/AC genotypes in VEGF RS1570360 and VEGF RS699947, respectively [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From our previous studies, we were able to highlight the significance of methylenetetrahydrofolate reductase (MTHFR 1298A > C) polymorphism as a possible risk factor for IVH due to increased levels of plasma homocysteine [35]. Similarly, there was approximately a 3.5-fold increased risk of developing IVH in preterm infants with the GT eNOS 894G > T polymorphism of endothelial nitric oxide synthase (eNOS), a gene associated with blood flow [12]. Prasun P et al examined polymorphisms in VEGF and showed a higher prevalence of IVH in infants with GA/AA and AA/AC genotypes in VEGF RS1570360 and VEGF RS699947, respectively [36].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the role of genetic factors in the pathophysiology of IVH will make it possible to determine the group of newborns who are specifically at risk of developing IVH in the perinatal period. The following genetic factors that may predispose to IVH have been analyzed so far: polymorphisms of genes coding for proinflammatory cytokines [7,8], coagulation pathway [9][10][11] regulation of systemic blood pressure and cerebral blood flows [12], as well as structural components of the germinal matrix [13,14]. There is still not enough definitive information about the connection between the increased risk of IVH and the molecular structure of the vasculature in the germinal matrix.…”
Section: Introductionmentioning
confidence: 99%
“…shown an independent association of Lys198Asn SNP of the EDN1 gene and number of diseases such as hypertension (Barath et al, 2007;Barbeau et al, 2003;Fang, Li, & Ma, 2017;Jin et al, 2003), obesity (Karita & Sadewa, 2019) (Colombo, Ciofini, Paradossi, Bevilacqua, & Biagini, 2006), diabetes (Li et al, 2008), pulmonary hypertension (Benza et al, 2015), intraventricular hemorrhage (SzpechtOctober , Gadzinowski, Seremak-Mrozikiewicz, Kurzawińska, & Szymankiewicz, 2016), and subarachnoid hemorrhage (Foreman et al, 2017;Gallek et al, 2013). Therefore, the Lys198Asn SNP is considered to be a risk factor for cardiovascular disease and cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NOS3 displays close association with endothelin function, as exemplified in the development of preterm infant intraventricular haemorrhage (via the association of NOS3 and endothelin-1 polymorphisms). 54 Dysfunctional NOS activity can lead to the development or potentiation of pathological states. A variety of SNPs in genes that regulate NOS and other downstream mediators in the nitric oxide pathway have been linked to vascular pathology.…”
Section: [H1] Endothelial Mechanismsmentioning
confidence: 99%